2007
DOI: 10.1007/s00159-007-0005-2
|View full text |Cite
|
Sign up to set email alerts
|

Non-thermal emission processes in massive binaries

Abstract: In this paper, I present a general discussion of several astrophysical processes likely to play a role in the production of non-thermal emission in massive stars, with emphasis on massive binaries. Even though the discussion will start in the radio domain where the non-thermal emission was first detected, the census of physical processes involved in the non-thermal emission from massive stars shows that many spectral domains are concerned, from the radio to the very high energies.First, the theoretical aspects… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
92
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 109 publications
0
92
0
Order By: Relevance
“…However, the reverse is not true; i.e., (many) massive binaries exist that show no signature of colliding winds. In fact, nonthermal radio emission is a rare feature (fewer than 40 cases in our Galaxy, see De Becker 2007;Benaglia 2010), and recent X-ray surveys have shown that most binaries are not significantly overluminous at high energies (Nazé 2009). Understanding why it is so will improve our knowledge of both collision mechanisms and stellar wind properties since such emissions heavily depend on them.…”
Section: Introductionmentioning
confidence: 94%
“…However, the reverse is not true; i.e., (many) massive binaries exist that show no signature of colliding winds. In fact, nonthermal radio emission is a rare feature (fewer than 40 cases in our Galaxy, see De Becker 2007;Benaglia 2010), and recent X-ray surveys have shown that most binaries are not significantly overluminous at high energies (Nazé 2009). Understanding why it is so will improve our knowledge of both collision mechanisms and stellar wind properties since such emissions heavily depend on them.…”
Section: Introductionmentioning
confidence: 94%
“…The models were aimed to describe the symbiotic systems and gamma-ray binaries, and also binary systems with O-type and Wolf-Rayet stars including the enigmatic object in η-Carinae. The colliding wind binaries were long known to be sources of non-thermal radio emission Eichler and Usov (1993), Dougherty et al (2005), Pittard and Dougherty (2006), De Becker (2007) and the catalog of colliding wind binaries with non-thermal particle acceleration compiled by De Becker and Raucq (2013) contains 43 objects.…”
Section: Colliding Wind Binariesmentioning
confidence: 99%
“…Second, in a number of cases non-thermal emission is observed (e.g. Dougherty & Williams 2000;van Loo 2005;De Becker et al 2006;van Loo et al 2006van Loo et al , 2008De Becker 2007;Nazé et al 2008;Montes et al 2009;Blomme et al 2010;A&A 570, A10 (2014) A prime example that fits into this class of X-ray and nonthermal radio emitting massive binary is the O+O-star system Cyg OB2#9 (van Loo et al 2008;Nazé et al 2008Nazé et al , 2010Volpi et al 2011). Our recent campaign to study this object has so far consisted of an analysis of optical and X-ray data by Nazé et al (2012b), and radio observations by Blomme et al (2013), which have refined the orbital solution and provided initial estimates for the stellar parameters − see Tables 1 and 2.…”
Section: Introductionmentioning
confidence: 99%